Some effects of motor-car driving on the normal and abnormal heart. Issue 5676 (18th October 1969) - Taggart, Peter; Gibbons, David; Somerville, Walter
Abstract : Electrocardiograms were recorded in experienced motor-car drivers accustomed to busy city traffic while driving their own cars along familiar routes. The majority with normal hearts or a history of coronary heart disease increased their heart rates; brief periods when the rate exceeded 140/min. were recorded in both groups. ST changes not caused by tachycardia developed in 3 out of 32 normal drivers. Of 24 drivers with coronary heart disease 13 increased their ST and T abnormalities, the changes being gross in six. A further five developed multiple ventricular ectopic beats. Two coronary drivers experienced anginal pain and two left ventricular failure. Healthy motor-racing drivers increased their heart rates to 180/min. in the few minutes before the start of a race and to above 200/min. while racing. Little or no change in the plasma catecholamine levels was noted in three coronary subjects immediately after a city drive compared with resting levels. All the racing drivers showed a considerable increase in noradrenaline, and in one instance adrenaline, immediately after racing. Persons in whom angina is easily provoked when driving or who are in borderline left ventricular failure should be advised not to drive.